(untitled) (International Journal of Food and Nutritional Sciences, 2023)
India is first in area for cotton cultivation and second in raw cotton production. The share of the India in cotton cultivation was 33.23% to the total area under cotton cultivation in the world. In India, debut GM variety of cotton increasing average yield from 326 kg/ha to 546 kg/ha in 2000 to 2014, respectively. Recent trend indicate, today need to develop the low initial cost mechanical harvesting system for cotton. The manual harvesting of cotton is time consuming and labor intensive. The manually operated pneumatic cotton picker had developed but it had low output capacity. To overcome the issues, develop a manual operated cotton picker. Evaluate performance of cotton picker, with varying the aspirator speed with varying the diameter pickup pipe. The three different pickup pipe of diameter 18 mm, 25 mm and 32 mm and three different speed of aspirator as 4500 rpm, 5500 rpm and 6500 rpm used.